Structure Changing in Maize-Based Agriculture Production in Vietnam: Case Study in Son La Province - Dang Thi Thanh Thuy; Nguyen Van Hieu (Warmadewa University Press, 2020)
Maize is the primary food resource for livestock, mainly cultivated in the northern mountains, the central provinces, and the central highlands in Vietnam. By studying reliable reports and policies related to maize-based agricultural production in combination with interviews and focus group discussion methods conducted in Son La province, this study specifically analyzes the situation of maize production in Vietnam and impacts of policies for the specific case in Son La province. The research results show that, though the sharp decrease, maize has still been the main crop with an annual cultivation area of ​​over 30% of the country's agricultural land recently. However, maize is only modestly mentioned in some central policies, and no policy at the local level is reserved for maize production. In addition, maize is no longer a crop to attract local farmers’ and authority’ interest, especially since 2015, the transition in maize cultivation area on sloping land to arable land of fruit trees and many other crops has been carried out on a large scale due to some policies by the province, resulting in a sharp decrease in maize cultivated area and production. This might lead to limited results of substantial government policies on maize acreage expansion, maize cultivated area planning, or maize development strategy. Accordingly, some recommendations to improve the situation are provided.